VALIDITAS DAN KEPRAKTISAN PANDUAN PRAKTIKUM INDIKATOR ASAM BASA BERBASIS GREEN CHEMISTRY DAN CHEMOENTREPRENEURSHIP UNTUK SMA/MA - fadillah vania arifah; Andromeda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Acid-base indicator practicum activities in schools have not been updated from year to year. The existing practicum guides have not been able to fully encourage the realization of graduate profile dimensions in accordance with the demands of the national curriculum. The existing acid-base indicator practicum guides in schools are not based on green chemistry and chemoentrepreneurship. Therefore, it is necessary to develop acid-base indicator practicum guides based on green chemistry and chemoentrepreneurship for senior high schools (SMA/MA). This study aims to develop acid-base indicator practicum guides based on green chemistry and chemoentrepreneurship for senior high schools (SMA/MA), as well as to determine the validity and practicality of the resulting products. The guide is designed by utilizing environmentally friendly natural indicators, and integrating the creation of simple products that have economic value by applying the concept of acid-base indicators. The development of this guide uses Educational Design Research (EDR) with the Plomp model which includes a preliminary research phase, and a prototype creation phase, consisting of self-evaluation, expert review, one-to-one evaluation, and small group. The product validity was conducted through several stages, namely expert review by five expert validators, one-to-one evaluation by three students, analyzed using the Aiken's V formula. Meanwhile, the practicality stage was assessed using a five-point Likert questionnaire filled out by nine students, analyzed using the percentage formula. The results showed that this guide was valid with an overall average Aiken's V of 0.9 covering aspects of content 0.935, presentation 0.91, language 0.88, and appearance 0.875. The practicality test showed an overall average percentage of 84.44%, categorized as very practical. These results indicate that the developed practical guide is valid and practical to support the learning process in the acid-base indicator sub-material in high school.